Analisis Engagement Sosial Media Akun Instagram @sef_id di Kota Pekanbaru - Roshiful Qolbi; Putri E. I. (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
Social media has become an essential part of modern society and is widely utilized as a platform for information dissemination, promotion, and audience relationship building. Instagram is one of the most widely used platforms for these purposes. However, an increase in the number of followers does not necessarily correspond to a higher level of audience engagement. This study aims to analyze the engagement level of the Instagram account @sef_id as a digital communication medium for the Student Education Forum (SEF) community in Pekanbaru City from the perspective of McQuail's New Media theory. This study employed a descriptive qualitative approach, with data collected through direct observation, documentation of Instagram Insights data, and a literature review. The findings reveal a significant digital gap. Although the @sef_id account consistently produced educational content and generated 11,742 views, it received only 184 interactions during the research period. The use of the Reels feature successfully expanded audience reach but failed to significantly increase audience interest and engagement. The low numbers of likes, comments, shares, and reposts indicate that communication remained predominantly one-way. Furthermore, the key characteristics of New Media—interactivity, social presence, privacy, and personalization—have not been optimally implemented through interactive features or persuasive Call to Action (CTA) strategies. Audience interaction increased when the account organized programs that encouraged direct participation. Therefore, a more interactive, personalized, and two-way digital communication strategy is needed to enhance engagement and enable Instagram to function more effectively as an organizational communication medium.